Chlorambucil-Induced Acute Interstitial Pneumonitis - Hammad Shafqat; Adam J. Olszewski (Case Reports in Hematology)
Chlorambucil is an alkylating agent commonly used in treatment of chronic lymphocytic leukemia (CLL). We report a case of interstitial pneumonitis developing in an 83-year-old man 1.5 months after completing a six-month course of chlorambucil for CLL. The interstitial pneumonitis responded to therapy with prednisone. We performed a systematic review of literature and identified 13 other case reports of chlorambucil-induced pulmonary toxicity, particularly interstitial pneumonitis. No unifying risk factor could be discerned and the mechanism of injury remains unknown. In contrast, major randomized trials of chlorambucil therapy in CLL have not reported interstitial pneumonitis as an adverse effect, which may be due to the rarity of the phenomenon or due to underreporting of events occurring after completion of treatment. Clinicians should consider drug-induced interstitial pneumonitis in the differential diagnosis of a suggestive syndrome developing even after discontinuation of chlorambucil.